Rapid Youth Assessment in Port Moresby, Papua New Guinea - Blank, Lorraine (World Bank, Washington, DC, 2017)
The objective of this rapid assessment is to inform the design of an Urban Youth Empowerment Project by providing information on youth and youth serving initiatives. Terms of reference crime and violence in Port Moresby and the National Capital District (NCD) are widespread and costly. In 2004, 68 percent of households reported that they had been victims of crime at least once in the past year and 51 percent had been victims of multiple crimes. Violence against women is pervasive, with domestic violence and rape, including gang rape, routine. By 2005, there had been small decreases in reported victimization; however, 61 percent of households still reported being victims of at least one crime and 46 percent reported being victims of multiple crimes. At the same time, costs associated with security and theft amounted to an estimated 15 percent of business turnover and law and order problems serve as a deterrent to investment. Young people account for the greatest share of crime and violence, so tackling the problem means addressing the underlying causes of youth crime and violence. This report provides a rapid assessment of youth and youth serving institutions in Port Moresby. The report relies on extensive consultations held in Port Moresby from July 23, 2008. Meetings were held with over 100 young people, their parents, community leaders, government officials, researchers, youth workers, leaders of youth groups and youth serving agencies, and representatives of the international non-governmental and donor agencies.